A Comparison of Rate of Dissolution of Different Sources of Phosphate Rock and Their Agronomic Effectiveness in Three Benchmark Soils of Ghana - Asomaning, S. K. (University of Ghana, 1999)
Soils of the semi-deciduous forest zone of Ghana are known to be moderately acid and very low in plant available phosphorus (P). These soils need to be fertilised to improve their potential for crop production. However high cost of commercial, water soluble fertilizers makes them beyond the reach of local farmers. Instead of expensive superphosphates, the use of less expensive phosphate rocks such as Togo rock phosphate (TRP), Gafsa rock phosphate (GRP) and 50% partially acidulated rock phosphate (PAPR- 50) are possible alternative P sources for these soils. A major limitation of phosphate rock (PR), however, is its inability to satisfy early requirement of available P due to its slow rate of dissolution. The objectives of this research were to compare the rate of dissolution of TRP, GRP, PAPR-50 and TSP and their agronomic effectiveness in three benchmark soils of Ghana ; Bekwai, Nzima and Kokofu. The dissolution of the P sources in the three soil series, was investigated in an incubation study Two-hundred grammes of each soil were incubated with TRP, GRP, PAPR-50 and TSP at a rate of 60 mg P kg' 1 soil. A control treatment with no addition of P source was also included. Incubation of the P sources in the various soils was done at 60% field capacity and at a temperature range of 20-25°C. The extent and rate of dissolution of the fertilizers, were determined by Anion Exchange resin Membrane (AEM) extraction in chloride form , 0.1M NaOH and 1M HC1 extractions at 21 days interval for 105 days. In a greenhouse study, each P source was added at the rate of 60 mg P kg' 1 soil, incubated for 7 days and sown to maize (Zea mays. var.Toxpino) for 28 days. The same variety of maize was sown in the field, in the three soils and the various P sources were applied at the rate of 60 kg P ha' 1 to evaluate the stubble and grain yield yield and also to determine the relative agronomic efficiency of the P sources with respect to the grain yield. The results of the incubation study showed that, the amount of P extracted by the AEM, (AEM-P) following the addition of GRP, PAPR or TSP decreased with time whereas TRP addition did not change with incubation time in all the three soils. There was a decrease in NaOH-Pi after a short period of incubation in both Bekwai and Nzima, the two well drained upper slope soils from the 3rd week to the 12th week followed by a slight increase in the rate of extraction as incubation progressed. In the lowland soil, Kokofu, there was a gradual increase from the 3rd week to the end of incubation period. In the case of HCl-extractable P, the HCl-Pi decreased between the 3rd and the 6th week, followed by a fairly uniform extraction with incubation period in all the three soils. The greenhouse results showed that in all the soils the following trend was observed in terms of dry matter yield: TSP = PAPR-50 > GRP > TRP. The relative agronomic efficiency (RAE) of the P sources compared with TSP also followed the trend: PAPR-50 > GRP > TRP. The field results indicated that, the application of the P fertilizers gave significantly high maize growth in the soils as a result of increased P uptake by the crop. Stubble yield, grain yield and the RAE followed the trend similar to what was obtained from the greenhouse. The main conclusion from the study was that TRP may have little or no potential for direct application because of its insolubility in these soils. However the PAPR-50 was found to be soluble enough to sustain maize growth and development and it may be prefered to TSP considering the high cost of the latter. It was inferred that the residues of PR and TSP in the Kokofu soil, long after first application can be more effective sources of P for plant growth than in the well drained upper slope, Bekwai and Nzima soils
Thesis (MPhil)-University of Ghana